Maribavir Pharmacokinetics and the Effects of Multiple-Dose Maribavir on Cytochrome P450 (CYP) 1A2, CYP 2C9, CYP 2C19, CYP 2D6, CYP 3A, N-Acetyltransferase-2, and Xanthine Oxidase Activities in Healthy Adults - Ma, Joseph D.; Nafziger, Anne N.; Villano, Stephen A.; Gaedigk, Andrea; Bertino, Joseph S. (Antimicrobial Agents and Chemotherapy, 2006)
Classifications Services AAC Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue AAC About AAC Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy AAC RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0066-4804 Online ISSN: 1098-6596 Copyright © 2014 by the American Society for Microbiology. For an alternate route to AAC .asm.org, visit: AAC